Efficient multiplex CRISPR/Cpf1 (Cas12a) genome editing system in Aspergillus aculeatus TBRC 277 - Abdulrachman, Dede; Champreda, Verawat; Eurwilaichitr, Lily; Chantasingh, Duriya; Pootanakit, Kusol (Journal of biotechnology, 2022)
CRISPR/Cas technology is a versatile tool for genome engineering in many organisms, including filamentous fungi. Cpf1 is a multi-domain protein of class 2 (type V) RNA-guided CRISPR/Cas endonuclease, and is an alternative platform with distinct features when compared to Cas9. However, application of this technology in filamentous fungi is limited. Here, we present a single CRISPR/Cpf1 plasmid system in Aspergillus aculeatus strain TBRC 277, an industrially relevant cell factory. We first evaluated the functionality of three Cpf1 orthologs from Acidaminococcus sp. BV3L6 (AsCpf1), Francisella tularensis subsp. novicida U112 (FnCpf1), and Lachnospiraceae bacterium (LbCpf1), in RNA-guided site-specific DNA cleavage at the pksP locus. FnCpf1 showed the highest editing efficiency (93 %) among the three Cpf1s. It was further investigated for its ability to delete a 1.7 kb and a 0.5 kb from pksP and pyrG genes, respectively, using two protospacers targeting these gene loci in a single crRNA array. Lastly, simultaneous editing of three sites within TBRC 277 genome was performed using three guide sequences targeting these two genes as well as an additional gene, kusA, which resulted in combined editing efficiency of 40 %. The editing of the NHEJ pathway by targeting kusA to generate a NHEJ-deficient strain of A. aculeatus TBRC 277 improved gene targeting efficiency and yielded more precise gene-editing than that of using wild-type strain. This promising genome-editing system can be used for strain improvement in industrial applications such as production of valuable bioproducts.CRISPR/Cas technology is a versatile tool for genome engineering in many organisms, including filamentous fungi. Cpf1 is a multi-domain protein of class 2 (type V) RNA-guided CRISPR/Cas endonuclease, and is an alternative platform with distinct features when compared to Cas9. However, application of this technology in filamentous fungi is limited. Here, we present a single CRISPR/Cpf1 plasmid system in Aspergillus aculeatus strain TBRC 277, an industrially relevant cell factory. We first evaluated the functionality of three Cpf1 orthologs from Acidaminococcus sp. BV3L6 (AsCpf1), Francisella tularensis subsp. novicida U112 (FnCpf1), and Lachnospiraceae bacterium (LbCpf1), in RNA-guided site-specific DNA cleavage at the pksP locus. FnCpf1 showed the highest editing efficiency (93 %) among the three Cpf1s. It was further investigated for its ability to delete a 1.7 kb and a 0.5 kb from pksP and pyrG genes, respectively, using two protospacers targeting these gene loci in a single crRNA array. Lastly, simultaneous editing of three sites within TBRC 277 genome was performed using three guide sequences targeting these two genes as well as an additional gene, kusA, which resulted in combined editing efficiency of 40 %. The editing of the NHEJ pathway by targeting kusA to generate a NHEJ-deficient strain of A. aculeatus TBRC 277 improved gene targeting efficiency and yielded more precise gene-editing than that of using wild-type strain. This promising genome-editing system can be used for strain improvement in industrial applications such as production of valuable bioproducts.